Questionnaire Study on Knowledge, Attitude and Practice on Factors Associated with Initiation and Cessation of Tobacco Among Patients Using Tobacco Products - J. Manju 1 , C. Krithika2 , Mutum Sangeeta Devi3 , P. Saranya4 , R. Saravanan BDS4 , N. Sanjana4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A study was conducted to assess the knowledge, attitude and practice (KAP) of factors associated withinitiation and cessation of tobacco among patients using tobacco products. A KAP study was conductedamong patients using tobacco products of various age groups attending the outpatient department in a dentalcollege in Chennai, Tamil Nadu. A self-constructed questionnaire by our team was framed and distributedto 100 subjects. The data collected was then analysed with SPSS software (version 21) statistically to obtainthe results.In this study, predominantly 69% of the subjects started the habit of using tobacco products in the agegroup of 15-25 years. Most commonly used tobacco product was cigarette (56%) and the frequency oftobacco usage was 5-10 times per day (50%). About 68% of the questioned subjects are aware of passivesmoking and 94% are aware of the consequences of using tobacco products. High prevalence of tobaccousage was observed among younger age group. This calls for the need that educational institutions mandatethe inclusion of awareness of health hazards of cigarette smoking in their curriculums. This is a much neededintervention to extricate them from this habit.